Dietary exposure to fatty acid esters of monochloropropanediols and glycidol of 2- to 3-year-old children attending nursery schools from two areas in China using the duplicate-diet collection method. Issue 1 (2nd January 2021) - Jiang, Liang; Jing, Zhou; Yibaina, Wang; Yan, Song; Lili, Xu; Yanxu, Zhong; Ling, Yong; Pingping, Zhou; Haixia, Sui; Lei, Zhang
ABSTRACT: The dietary exposures to fatty esters of 3- and 2-monochloropropanediol (MCPD) and glycidol were estimated for children aged 2- to 3-year-old from two areas of China using duplicate diet collection method. The 24-h daily duplicate diet samples over three consecutive days were collected from 40 healthy children aged between 26 and 36 months. The analysis of these contaminates in food samples was measured by an indirect method that entails MCPD/glycidol cleavage from their esterified forms for GC-MS analysis. Over 71% of the mixed diet and dairy products samples were found to be contaminated with 3-MCPD and glycidyl esters. The estimated daily exposure to bound 3-MCPD (mean: 0.48–0.49 μg kg −1 bw day −1 ; P95: 1.00–1.11 μg kg −1 bw day −1 ) were well below the health guidance values and were considered of low safety concern. The daily exposure to bound 2-MCPD was estimated to be 0.031–0.038 μg kg −1 bw day −1 on average and 0.12–0.14 μg kg −1 bw day −1 for the P95 exposure. However, it was not possible to assess its risk due to the lack of health guidance value of 2-MCPD. The margin of exposure (MOE) estimates for the mean exposure to bound glycidol (0.10–0.12 μg kg −1 bw day −1 ) were far above 10000 and were considered of low safety concern. However, the margin of exposure estimates for the P95 bound glycidol exposure (0.41–0.45 μg kg −1 bw day −1 ) were below 10000 and indicated a health concern. Our data indicated that the mixed diet accounted for nearly 76% to 91% of bound MCPD and glycidol exposure. In addition, the follow-on formula was also an important source for the children aged 2–3 years.